Peran Kearifan Lokal dalam Mendukung Kebijakan Perlindungan Mata Air untuk Mewujudkan FOLU Net Sink di Nusa Tenggara Barat Indonesia - Alamsyah, Fajar; Wijaya, Andy Fefta; Lastiti Veri Anggaini, Niken (Jurnal Ilmiah Administrasi Publik, 2025)
Water scarcity is a global issue with serious impacts on health, food security, and the environment. In West Nusa Tenggara (NTB), Indonesia, deforestation and land degradation have reduced water availability, leading to decreased agricultural productivity and increased disease risks. This study employs a qualitative approach through Systematic Literature Review (SLR) to analyze the role of NTB's local wisdom, such as Leka Dana in Dompu and Parafu in Bima, in supporting spring protection policies and contributing to the FOLU Net Sink 2030 target, which aims to make the forestry sector a net carbon sink. The SLR method involved identification, selection, and critical appraisal of scholarly articles, research reports, and other relevant sources. Findings reveal that these traditional practices have effectively maintained water resource sustainability and ecosystem balance. However, integration of local wisdom into national policies remains limited. Based on these findings, the study recommends three strategic measures, first, increasing community participation; second, strengthening customary institutions; and third, integrating traditional knowledge into modern environmental policies. Implementation of these recommendations is expected to support sustainable water resource management in NTB.